THE APPLICATION OF INQUIRY METHOD IN WRITING DESCRIPTIVE TEXT FOR SEVENTH GRADE STUDENTS - Emiliya Sukma Dara Damanik; Fitri Amalia; Rocky Arya Pradika (PRIMACY Journal of English Education and Literacy, 2022)
The aim of this research is to describe how the method technique is used in producing descriptive writings in class VII Junior High School Medan. This study examines the use of the inquiry method in producing descriptive writings, as well as the impacts of the method's use and the challenges English teachers experience when using it in class VII SMP Medan. This study use descriptive qualitative research. The subject of this study is students of class VII of Junior High School Medan. The object of this research is to learn to write description text with inquiry method. The information gathered came from a variety of sources, including events, informants, and records. To clarify the effects of the application of inquiry method and the problems faced by English teachers in applying this method. Data was collected through observations, interviews, and documents from writing learning activities. According to the findings of this study, the following are the result of applying inquiry method in writing descriptive text: (1) make students has learning experience that demands independence, critical, creative, and innovative. And another result about problems that faced by teacher in applying inquiry method in writing descriptive text include: (1) different capability of the students that can be see when the teacher explained the materials, (2) the lack of vocabulary, and (3) students are less prepared to enter English class with not bring dictionary.